2011
DOI: 10.1007/s11676-011-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Nursery practice on seed germination and seedling growth of Dalbergia sissoo using beneficial microbial inoculants

Abstract: Nursery practice using microbial inoculants was performed to find out the efficacy of the inoculants on seed germination and seedling growth of sissoo (Dalbergia sissoo Roxb.). Microbial inoculants or effective microorganisms (EM) are a mixture of many different beneficial microorganisms in a solution. The seedlings were grown in a mixture of sandy soil and cowdung (3:1) kept in polybags with pouring EM solution at different concentrations (0.1%, 0.5%, 1%, 2%, 5% and 10%) before and after a week of sowing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…But the influence of MI on forest crops has not been studied widely (Khan et al, 2006(Khan et al, , 2011. From this study, it has been observed that soil amended with different concentrations of MI can also improve the seedling growth of forest crops.…”
Section: Germination and Seedling Growthmentioning
confidence: 90%
See 4 more Smart Citations
“…But the influence of MI on forest crops has not been studied widely (Khan et al, 2006(Khan et al, , 2011. From this study, it has been observed that soil amended with different concentrations of MI can also improve the seedling growth of forest crops.…”
Section: Germination and Seedling Growthmentioning
confidence: 90%
“…From this study, it has been observed that soil amended with different concentrations of MI can also improve the seedling growth of forest crops. Mridha (2005), Khan (2012) and Khan et al (2011Khan et al ( , 2014) also reported enhanced seed germination rate and seedling growth with the application of low concentrations of MI. Specially, applying 2% of MI enhanced seed germination and seedling growth at an optimum level which might be due to the presence of microbial population in such a density within this concentration which was cable to produce optimum level of growth enhancing hormones and other chemicals.…”
Section: Germination and Seedling Growthmentioning
confidence: 95%
See 3 more Smart Citations